Ubiquitin-Fold Modifier-1 Participates in the Diabetic Inflammatory Response by Regulating NF-κB p65 Nuclear Translocation and the Ubiquitination and Degradation of IκBα - Hu X; Zhang H; Zhuang L; Jin G; Yang Q; Li M; Sun W; Chen F (Dove Medical Press, 2020)
Xiaolei Hu, 1 Hengyan Zhang, 1 Langen Zhuang, 1 Guoxi Jin, 1 Qingqing Yang, 1 Min Li, 1 Weihua Sun, 1 Fengling Chen 2 1Department of Endocrinology, The First Afﬁliated Hospital of Bengbu Medical College, Bengbu, Anhui 233004, People’s Republic of China; 2Department of Endocrinology, Shanghai Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai 200011, People’s Republic of ChinaCorrespondence: Xiaolei HuDepartment of Endocrinology, The First Afﬁliated Hospital of Bengbu Medical College, Bengbu, Anhui 233004, People’s Republic of ChinaTel +86-0552-3086113Email caesar80@163.comFengling ChenDepartment of Endocrinology, Shanghai Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai 200011, People’s Republic of ChinaTel +86-021-56691101Email Prof_flchen@163.comBackground: Ubiquitin-fold modifier-1 (Ufm1) is a recently identified ubiquitin-like protein. We previously confirmed that Ufm1 expression was increased in diabetic mice. However, its role in the development of diabetes remains undefined.Methods: Lentivirus-mediated gene knockdown and overexpression techniques were used to observe the effect of Ufm1 on the expression of inflammatory factors, adhesion molecules and chemokines, as well as the transcriptional activity of nuclear factor kappa-B (NF-κB) in macrophages. Western blot and immunofluorescence analyses were used to analyse the mechanism by which Ufm1 affects the transcriptional activity of NF-κB. Finally, the effects of Ufm1 on inflammation and pancreatic, renal and myocardial damage were observed in db/db mice.Results: Knockdown of Ufm1 by lentivirus shRNA targeting Ufm1 (Lv-shUfm1) led to decreased secretion of IL-6, IL-1β, ICAM-1, VCAM-1, MCP-1 and CXCL2 in RAW264.7 cells that were exposed to LPS and TNF-α, while lentiviral overexpression of Ufm1 (Lv-Ufm1) caused the opposite effect. Interestingly, further investigation indicated that Ufm1 induced NF-κB p65 nuclear translocation in RAW264.7 cells via increasing the ubiquitination and degradation of IκBα. In an in vivo experiment, pretreatment of db/db mice with Lv-shUfm1 reduced the mRNA levels of TNF-α, IL-6, IL-1β, ICAM-1, VCAM-1, MCP-1 and CXCL2 in resident peritoneal macrophages (RPMs) and decreased the plasma levels of TNF-α, IL-6, IL-1β, ICAM-1, VCAM-1, MCP-1 and CXCL2. Additionally, in Lv-Ufm1-treated mice, the inverse results were observed. Following treatment with Lv-shUfm1 and Lv-Ufm1, NF-κB p65 nuclear translocation in RPMs was decreased and increased, respectively. Importantly, we observed that Lv-shUfm1 injection led to a decrease in plasma glycaemia, a reduction in urinary albuminuria and cardiomyocyte hypertrophy and an improvement in the histopathological appearance of pancreatic, kidney and myocardial tissue. Pretreatment of the mice with Lv-shUfm1 inhibited macrophage infiltration in the pancreas, kidney and myocardial tissue.Conclusion: Our data elucidate a new biological function of Ufm1 that mediates inflammatory responses. Ufm1-mediated p65 nuclear translocation occurs by modulating the ubiquitination and degradation of IκBα. Moreover, downregulating Ufm1 is an effective strategy to prevent the development of type 2 diabetes and its complications.Keywords: ubiquitin-fold modifier-1, macrophage, NF-κB, IκBα, diabetes, diabetic complications